Kekerasan Dalam Rumah Tangga Persepektif Hukum Keluarga Dan Perlindungan HAM - Muhammad Nadhiful Hakim; Syakir An'umillah Syaefudin (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Domestic violence is a serious problem that violates human rights and affects the lives of many individuals in various countries, including Indonesia. The protection of human rights and the enforcement of family law are crucial in addressing this issue. The implementation of existing laws, cooperation between various relevant institutions, and education of the public about this issue are necessary steps to protect victims and prevent domestic violence. This research uses a literature review method to collect data and information from various literature sources relevant to the topics of family law and human rights protection in the context of domestic violence. The results show that domestic violence is a serious problem that needs to be addressed through effective protection and prevention efforts, including through laws, public education, and women empowerment.